A novel hybrid and interactive solar system consists of Stirling engine ̸vacuum evaporator ̸thermoelectric cooler for electricity generation and water distillation. (June 2020) - Al-Nimr, Moh'd A.; Al-Ammari, Wahib A.
Abstract: This paper introduces a novel hybrid and interactive solar system to generate electricity and produce desalinated water. The system consists of a Stirling engine driven by concentrated solar radiation and cooled by saline water. Also, the system consists of an evacuated evaporator chamber to evaporate the saline water and thermoelectric cooler, driven by Stirling engine, to condensate the distilled water. The novelty of the system is in its positive interactivity since each component and product enhances the performance and productivity of others. The rejected heat from both the cold side of Stirling engine and the hot side of the TEC modules is used to heat the saline water before entering the evaporator. Also, the cold side of the TEC modules is used to enhance the condensation and hence the desalination rate. The importance of the second enhancement technique relays in the fact that many applications do not suffer from the absence of hot evaporative heating sources but suffer from the absence of condensation cool surfaces. A steady-state mathematical model has been proposed and validated by being compared with published data. The results show that at an optimized design point (solar radiation of 700 W/m2, wind speed of 5 m/s, swept volume of 210 cm 3, dish diameter of 2.68 m, etc.), the overall efficiency of the system was 65.8% with a net output power of 506 W and desalinated water of 28 kg/day. Including the TEC system has enhanced the condensation rate from 2.93 kg/day to 34.14 kg/day and the efficiency from 22.84% to 54.87%. Also, the two preheating effects (rejected heat from Stirling engine and from TEC modules) enhance the desalination rate from 2.93 kg/day to 11.74 kg/day and efficiency from 22.84% to 34.53%. Combining both enhancement techniques increase the desalination rate from 2.93 kg/day to 40.96 kg/day and efficiency from 22.84% to 64.44%. Highlights: A novel hybrid and interactive solar system is introduced. Solar Stirling engine, thermoelectric cooler and vacuum evaporator were integrated. The novelty of the system is in its positive interactivity between all components. At optimum point, a 506 W of electricity and 28 kg/day of fresh water are obtained. Integrating TEC modules increases the overall efficiency from 22.84% to 54.87%.